ANALYSIS OF FINANCIAL MANAGEMENT OF VILLAGE OWNED ENTERPRISES - Septia Asliyanni; Heny Triastuti K; Lusi Elviani Rangkuti; Sri Rahayu; Nasma Tia Miswari; Suginam (International Journal of Accounting, Finance and Business, 2023)
The purpose of this study is that researchers want to find out the implementation of village- owned enterprise (BUMDes) financial management in Denai Lama Village, Pantai Labu District, Deli Serdang Regency based on Village Minister Regulation number 3 of 2021. This type of research uses qualitative research methods using a descriptive and study approach. cases obtained from interviews with trusted sources at BUMDes Sastro 3-16. The data analysis method goes through several stages, namely data reduction, data presentation, verification conclusions are drawn. The results of this study are that the financial management carried out by BUMDes is still simple. The Planning Stage is carried out by holding deliberations for each unit to form a Draft Budget. The implementation phase is carried out using receipts as proof of disbursement of funds. The Administration stage is carried out by recording cash inflows and disbursements. The Accountability Stage is carried out in an accountable and accountable manner, this accountability stage has also been carried out twice in one year. The Supervision Stage is carried out with supervision carried out by the BPD. So, the Administration Stage and Supervision Stage are still not in accordance with Village Minister Regulation Number 3 of 2021.